Implementation Double Exponential Smoothing (DES) Method and Economic Order Quantity(EOQ) Probabilistic Method in Plam Oil Inventory Control - Azhari Alim Bahri; Nur Zakia Hsb (Journal Of Management Analytical and Solution (JoMAS), 2025)
In a company, inventory processing is very important. For this reason, it is necessary to control inventory in order to minimize costs for the benefit of the company. In this study, the authors use the DES method which aims to forecast palm oil demand for  2020 and the Probabilistic EOQ method which can minimize the cost of palm oil inventory at PT. Nusantara IV Medan Plantation. The effectiveness of the Double Exponential Smoothing Method is seen from the minimum MAPE value of 0.29541 which is at an alpha of 0.8. Based on the calculations and data processing carried out, the results of forecasting the demand for palm oil in 2020 were obtained at 483,699,862 Kg with an average demand of 48,369,986 Kg. Based on the Probabilistic EOQ method, the optimal number of orders for palm oil is 8,840,057,829 Kg with an order frequency of 55 times/year with an ROP of 994,798,8395 Kg and the total cost of palm oil inventory is Rp. 79,551,503,603.